2021
DOI: 10.1099/mgen.0.000721
|View full text |Cite
|
Sign up to set email alerts
|

Genomic comparisons of Escherichia coli ST131 from Australia

Abstract: Escherichia coli ST131 is a globally dispersed extraintestinal pathogenic E. coli lineage contributing significantly to hospital and community acquired urinary tract and bloodstream infections. Here we describe a detailed phylogenetic analysis of the whole genome sequences of 284 Australian ST131 E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 94 publications
(182 reference statements)
3
46
0
Order By: Relevance
“…pUTI89-like plasmids were confined to phylogroups B2 and D and were most common in ST963 (8/9, 89%), ST95 (3/6, 66.7%), and ST131 (5/8, 62.5%) sequences. Their presence in these STs is indicative of sublineage partitioning, as has been recently described for ST131 and ST95 ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…pUTI89-like plasmids were confined to phylogroups B2 and D and were most common in ST963 (8/9, 89%), ST95 (3/6, 66.7%), and ST131 (5/8, 62.5%) sequences. Their presence in these STs is indicative of sublineage partitioning, as has been recently described for ST131 and ST95 ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 69%
“…The major human ExPEC STs, particularly ST95 ( 22 ), ST131 ( 23 , 26 ), and ST73 ( 45 ), comprise sublineages that are often discernible by serotype and fimH allele variation. Lineage subdivision is also often accompanied by carriage of different F plasmid replicon sequence types belonging to ColV (various replicon types) and pUTI89-like (ColIa + /F29:A-:B10) genotypes ( 22 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whole-genome analysis revealed a large cluster belonging to fimH41 ST131. A recent study in Austria also reported cross-species transmission (synanthropic birds and humans) in fimH41 ( Li et al, 2021 ). Our study supports the “one health” concept ( Murphy et al, 2010 ; Trinh et al, 2018 ; Collignon and McEwen, 2019 ) that the same clone of fimH41 ST131 circulates among humans, dogs, and the environment.…”
Section: Discussionmentioning
confidence: 90%